Lack of robust evidence for a Wolbachia infection in Anopheles gambiae from Burkina Faso. Issue 3 (25th July 2022) - Sawadogo, Simon P.; Kabore, Didier A.; Tibiri, Ezechiel B.; Hughes, Angela; Gnankine, Olivier; Quek, Shannon; Diabaté, Abdoulaye; Ranson, Hilary; Hughes, Grant L.; Dabiré, Roch K.
Abstract: The endosymbiont Wolbachia can have major effects on the reproductive fitness, and vectorial capacity of host insects and may provide new avenues to control mosquito‐borne pathogens. Anopheles gambiae s.l is the major vector of malaria in Africa but the use of Wolbachia in this species has been limited by challenges in establishing stable transinfected lines and uncertainty around native infections. High frequencies of infection of Wolbachia have been previously reported in An . gambiae collected from the Valle du Kou region of Burkina Faso in 2011 and 2014. Here, we re‐evaluated the occurrence of Wolbachia in natural samples, collected from Valle du Kou over a 12‐year time span, and in addition, expanded sampling to other sites in Burkina Faso. Our results showed that, in contrast to earlier reports, Wolbachia is present at an extremely low prevalence in natural population of An . gambiae . From 5341 samples analysed, only 29 were positive for Wolbachia by nested PCR representing 0.54% of prevalence. No positive samples were found with regular PCR. Phylogenetic analysis of 16S rRNA gene amplicons clustered across supergroup B, with some having similarity to sequences previously found in Anopheles from Burkina Faso. However, we cannot discount the possibility that the amplicon positive samples we detected were due to environmental contamination or were false positives. Regardless, the lack of a prominent native infection in An . gambiae s.l. is encouraging for applications utilizing Wolbachia transinfected mosquitoes for malaria control. Abstract : The natural infection of endosymbiont Wolbachia was re‐evaluate in Anopheles gambiae s.l. from Burkina Faso. Wolbachia is present at an extremely low prevalence in natural population of An. gambiae s.l. Regardless, the lack of a prominent native infection in An. gambiae s.l. is encouraging for applications utilising Wolbachia transinfected mosquitoes for malaria control.